Effects of Intravitreal Ranibizumab Injection on Chinese Patients with Wet Age-Related Macular Degeneration: 5-Year Follow-Up Results - Yingyi Lu; Jianfeng Huang; Jing Zhao; Xiaobing Yu; Li Long; Hong Dai (Journal of Ophthalmology)
Purpose. To observe the effect of intravitreal ranibizumab injection on wet age-related macular degeneration (wAMD) over 5 years in Chinese patients. Methods. Thirty-seven patients who were diagnosed with wAMD in our hospital from June 2007 to June 2014 were retrospectively reviewed. The PRN regimen and the treatment and extend regimen were applied. Best corrected visual acuity (BCVA), number of ranibizumab injections, and changes in the choroidal neovascularization (CNV) lesion over 5 years were analyzed. Results. The mean BCVA measured by the ETDRS chart at baseline was 47.4 and 5 years after the treatment it was 34.89 letters, which was significantly different (p=0.013). Fourteen eyes (37.8%) had improved visual acuity after 5 years. The number of injections in 5 years was 11.53, and most of the injections were in the first two years. Seventeen (45.9%) cases developed fibrous lesions, and 2 (5.4%) cases had atrophic lesions after 5 years. The fibrosis/atrophy was significantly correlated with the injection numbers (Pearson, r=0.663, and p=0.000). Conclusion. Most of the patients can maintain visual acuity treated by ranibizumab in the first 3 years. After 5 years, some patients can still improve or maintain visual acuity. Fibrous scarring of the lesion is the main reason for a decrease in vision of wAMD patients.